Patient Analisis Kujungan Pasien Pada Kualitas Pelayanan di RSU Fikri Medika Karawang, (Studi Kasus Masa Pandemi Covid – 19 tahun 2019 – 2021) Jl. Raya Kosambi-Tegalsari Km 3 Klari, Karawang, Jawa Barat: Service Quality - rustomo (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2022)
This study analyzes the process or efforts of processing data into new information so that the characteristics of the data become easier to understand and useful as a solution to a problem. The data is described quantitatively as a result of data collection from the source as part of the information. This study aims to analyze the data that has been presented at RSU Fikri Medika Karawang to make new information in order to improve the quality of service for the achievement of the hospital's vision and mission to increase the volume of patient visits. RSU Fikri Medika Karawang needs to detect early with the number of patients visiting by gender, age and occupation as an early anticipation to ensure patient satisfaction. From the distribution of questionnaires to 100 respondents that female patients of productive age and on average are farmers and traders, it is a challenge for the management of Fikri Medika Hospital Karawang to ensure the existing quality. With 18 statements that were shared with the google questionnaire, the results of the instrument test on the decision were valid and the consistency value was greater than the specified standard.